Exploring Students’ Meaning-Making Strategies in Indonesian–Arabic Translation: A Qualitative Inquiry - Azwir, Azwir (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
Translation in higher education, particularly in Indonesian–Arabic contexts, involves complex cognitive and interpretive processes that go beyond linguistic transfer. However, previous studies have largely focused on translation products rather than the process of meaning-making. This study aims to explore students’ cognitive and interpretive approaches in constructing meaning prior to translation. A qualitative exploratory design within an interpretive paradigm was employed, involving undergraduate students of Arabic language and translation studies. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that students employ various cognitive strategies, including global reading, inferencing, syntactic analysis, and segmentation, alongside interpretive strategies such as contextualization, intention-based interpretation, and cultural adjustment. The study also finds that students demonstrate metacognitive awareness through meaning prioritization, strategic combination, and self-monitoring. These findings suggest that translation is a process-oriented activity driven by meaning construction rather than direct language transfer. The study concludes that emphasizing students’ meaning-making processes can enhance translation learning and support the development of more effective pedagogical approaches.